The boxing baroness - Spencer, Minerva (Wicked women of Whitechapel, 2022)
"Magnetic and educated, Marianne Simpson has the manner of a lady and the looks of a lover, not a fighter. Neither of which explains her occupation as a boxer in her uncle's circus, Farnham's Fantastical Female Fayre. Nonetheless, when St. John Powell, the exquisitely handsome Duke of Staunton, begins turning up at her shows, she finds herself dangerously distracted by the powerful peer's mysterious presence. With her safety at stake, Marianne's days in the ring are numbered. But how long can she fight her attraction to the man the ton calls Lord Flawless? St. John Powell doesn't just want Marianne Simpson, he needs her... to rescue his brother, who is being held for ransom by a treasonous English baron--the man all of Britain knows as the Rake of Rakes. No matter how little Marianne wants to see her duplicitous ex-lover, the man responsible for the humiliating nickname the Boxing Baroness, St. John must convince her. Even if it means climbing into the ring with the beautiful boxer and taking everything she's got..."--